Hubungan Pengetahuan Gizi dan Tingkat Kecukupan Zat Gizi dengan Status Gizi Peserta Didik Kelas XI MIPA di SMAN 2 Maros - Wahdaniyyah Wahdaniyyah; A. Mushawwir Taiyeb; Hartono Hartono (Universitas Negeri Makassar, 2022)
This study aims to determine the relationship between nutritional knowledge and nutritional adequacy levels with the nutritional status of students in class XI MIPA at SMAN 2 Maros. This research is a descriptive correlational research. The research population is all students of class XI MIPA at SMAN 2 Maros as many as 76 people. The sampling technique is a total sampling technique by making all members of the population a sample. Data were analyzed descriptively and inferentially using partial correlation test and multiple correlation test. The results of this study indicate that there is a relationship between nutritional knowledge and the level of nutritional adequacy with the nutritional status of students with a significance value of 0.000 <0.05. The evenness of the relationship is in the